Orientation formation of the fire cement mineral phase from Dolomite-Alumina compositions - Abdul Rachman; Suhanda Suhanda; Muhammad Syaifun Nizar (Balai Besar Keramik, 2017)
The formation of the mineral phase of fine cement type mixture of calcium aluminate and magnesium aluminate has been made of a mixture of fine dolomite and alumina materials. The composition defined by cross system comparisons (75, 50, 25 : 25, 50, 75) % with the conditions and constant firing temperature 1200oC. Characterization of the test sample fired product include XRD, chemical analysis, and physical analysis, which showed the formation of the main mineral phases of calcium aluminate, magnesium aluminate and free alumina. The type and level of calcium aluminate phase stability of the composition is varied than magnesium aluminate phase; among the others forming grossit (CaAl4O7) for Al2O3 content of excess (code C) and Ca3Al2O6 for excess CaO constant (code A). Physical properties of the two types of cement fine in succession, the density are 2,0 and 2,5 gr/cm3, the porosity are 24,42 and 52,23 %, pH 10 and 8, the compression strength are 150 and 160 / 2 cm diameter of test pieces. The selected composition (C) is the best of the cement product made of dolomit -alumina. The purpose of the orientation of fire cement mineral phase formation, is to give direction forming system fire cement mixture CA / MA of dolomit alumina in the system (CaO-MgO-Al2O3) is controlled minerology and physics.